2004
DOI: 10.1111/j.1601-5223.1996.t01-1-00031.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomes and their Meiotic Behavior in Two Families of the Primitive Infraorder Dipsocoromorpha (Heteroptera)

Abstract: Five species belonging to the two families of Dipsocoromorpha were studied: three species from the family Dipsocoridae ~ Cryptostemma pusillimum J . Sb. (2n = 16 + 2m + XY, Yz), C. hickmani Hill (2n = 18 + 2m + XU), and C. ca.ytuneouitreus Linnavuori (2n = 18 + m? + XU) and two species from the family Schizopteridae Pateenu elimata Hill (2n = 30 + 2m + X O ) and Rectilamintl australis Hill (2x1 = 30 + 2m + X0). In all species, autosomes formed chiasmate bivalents in spermatogenesis, and the sex chromosome uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 8 publications
0
69
0
3
Order By: Relevance
“…Heteroptera chiasmata distribution and frequency data show that they are located terminally and that there is a predominance of one chiasma per bivalent (Satapathy and Patnaik, 1988;González-Garcia et al, 1996;Grozeva and Nokkala, 1996;Bressa et al, 1999;Nokkala and Nokkala, 1999), although subterminal chiasmata have been observed in some species and two chiasmata have been noted in some bivalents (Camacho et al, 1985;Mola and Papeschi, 1993;Nokkala and Nokkala, 1997;Rebagliati et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Heteroptera chiasmata distribution and frequency data show that they are located terminally and that there is a predominance of one chiasma per bivalent (Satapathy and Patnaik, 1988;González-Garcia et al, 1996;Grozeva and Nokkala, 1996;Bressa et al, 1999;Nokkala and Nokkala, 1999), although subterminal chiasmata have been observed in some species and two chiasmata have been noted in some bivalents (Camacho et al, 1985;Mola and Papeschi, 1993;Nokkala and Nokkala, 1997;Rebagliati et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…To study the number and behavior of chromosomes, the preparations were stained following the Schiff-Giemsa method developed by Grozeva, Nokkala (1996). The preparations were fi rst subjected to hydrolysis in 1 N HCl at room temperature for 20 min, then in 1 N HCl at 60°C for 8 min, and stained in Schiff's reagent for 20 min.…”
Section: Standard Stainingmentioning
confidence: 99%
“…Standard staining For standard staining the method of Grozeva and Nokkala (1996) was used. The prepara-Comp.…”
Section: Chromosome Preparationsmentioning
confidence: 99%